Associations between sedentary behavior, physical activity frequency, and asthma: insights from the National Health and Nutrition Examination Survey 2009-2018 - Yanhao Chen; Xiang Li; Mengqi Wu; Jiaqi Peng; Jiao Zhang; Jie Bao; Yongsheng Fan; Shuo Huang (Monaldi Archives for Chest Disease)
This study aimed to explore the relationship between sedentary time and asthma prevalence and to examine the relationship between physical activity, sedentary behavior, and asthma symptom improvement among individuals with a history of asthma. As a cross-sectional study, the associations observed do not imply causation. Utilizing data from five survey cycles (2009-2018), the study analyzed sedentary time and physical activity frequency using multivariate logistic regression and generalized additive models. Subgroup analyses and interaction tests evaluated demographic influences on the relationship between sedentary behavior and asthma. Results indicated that extended sedentary behavior was significantly associated with a higher likelihood of asthma, with individuals sitting more than 8 hours daily having 35% greater odds of having asthma. Reduced sedentary time and moderate physical activity may be associated with a lower likelihood of reporting current asthma, with a significant reduction observed when moderate activity occurred ≤2 times per week.